Pengaruh Metode Aptitude Treatment Interaction (ATI) Terhadap Hasil Belajar Pendidikan Agama Islam - Nasution, Sumiah; Arifin, Muhammad (Jurnal Gemaedu, 2019)
The purpose of this study was to determine the extent of the effect of the aptitude treatment interaction (ATI) method on the learning outcomes of Islamic Education on the fifth grade students of Cipondoh Makmur State Elementary School Tangerang. The research method used is the experimental method with analysis of normality testing using the Chi Square Test technique that is testing data in the form of group data. The benefits of this study are to add to the repertoire of education, especially for Islamic Education subjects in an effort to improve and grow the quality of national education. The results showed that there was a significant effect between the aptitude treatment interaction (ATI) method on the learning outcomes of Islamic Education and it was proven from the results of the t test to show t-count> t-table, which is 24.55> 1.67.